MAPPING AFFECTIVE URBAN ATMOSPHERES IN SHANGHAI’S PUBLIC TRANSPORTATION: A METHODOLOGICAL APPROACH TO URBAN MOBILITIES - Atteneder, Helena; Rodriguez-Amat, Joan Ramon (AoIR Selected Papers of Internet Research, 2026)
Urban spaces are shaped by affective atmospheres, emerging from the interplay of material, social, and digital components. Digitalization and ‘smart’ urban infrastructures introduce new dynamics, affecting how people experience and navigate urban environments. This study investigates the role of mobile media in shaping affective urban atmospheres within Shanghai’s public transport system, conceptualizing mobility as both a physical and digital process embedded in socio-political power structures. Public transport operates as a hybrid space where movement of people, goods, and information converge. While data-driven mobility systems aim to enhance efficiency, they often neglect the affective dimensions of urban life. Research suggests that digital media and mobile technologies significantly shape urban atmospheres, influencing behavior and emotions in public spaces. This study, grounded in Non-Representational Theory and Affect Theory, develops a methodological toolset to systematically capture and visualize these atmospheres. The research, conducted in Shanghai (April 2024), integrates GPS tracking, geolocated images, sniffer data for digital signal detection, and ethnographic field notes. By synchronizing these data sources, the study visualizes urban affective densities using heat maps and spatial analyses. Findings reveal that public transport atmospheres are shaped by a dynamic interplay of digital and material elements, offering new insights into mobility practices and urban social interactions. This study contributes to research on public space and mobility while informing urban planning strategies. It highlights the need to incorporate affective atmospheres into smart city policies, ensuring urban mobility enhances both efficiency and quality of life.